(untitled) (Archives of Pediatrics of Uruguay, 2022)
We hereby present joint recommendations for cardiovascular assessment of people under 35 years of age who do exercise and sports. We set the guidelines regarding evaluation and score of such assessment, the agents in charge of implementing it and the main components of a correct cardiovascular assessment. We take into account the family and personal history and perform a comprehensive physical examination as well as an ECG as a mandatory part of this comprehensive approach. We mention other optional functional studies as well as reference to specialists whenever necessary.